Factors Affecting the Implementation of OSH in Nurses in the Emergency Department of RSUD dr. Soedarso West Kalimantan Province in 2025: FAKTOR YANG MEMENGARUHI PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PERAWAT DI INSTALASI GAWAT DARURAT (IGD) RUMAH SAKIT UMUM DAERAH DOKTER SOEDARSO PROVINSI KALIMANTAN BARAT TAHUN 2025 - Marihot Manurung, Togu; Rahmad Gurusinga; Layari Tarigan; Lastiurma Manurung; Bintang Kasih Manurung (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Occupational Safety and Health (OSH) is a crucial aspect of workforce management to create a safe, healthy, and productivity-supporting work environment. In the healthcare sector, the implementation of OSH is particularly vital, especially for health workers such as nurses who often face various occupational risks. Objective: This study aims to identify the factors influencing the implementation of OSH among nurses in the Emergency Department of Dr. Soedarso Regional Public Hospital. Research Method: This study used an analytical survey method with a cross-sectional approach. The sample consisted of 34 nurses working in the Emergency Department, selected using total sampling technique. Data analysis was performed using the chi-square test and multivariate analysis through logistic regression. Results: The study showed that the predisposing factor of work experience was not significantly associated with OSH implementation (0.300 > 0.05), while predisposing factors such as knowledge (0.007 < 0.05) and attitude (0.037 < 0.05), as well as the enabling factor of facilities (0.037 < 0.05), were significantly associated with OSH implementation. The hospital is expected to select nurses with longer work experience in accordance with their expertise, organize seminars and training, conduct supervision, provide supporting Occupational Safety and Health (OSH) facilities, and carry out regular evaluations. These steps aim to improve the quality of nursing staff and encourage better and more positive OSH implementation in the hospital's emergency department.